SHIFT IN HUMAN ROTAVIRUS DISTRIBUTION IN BELO HORIZONTE, BRAZIL DETECTED BY RIBONUCLEIC ACID ELECTROPHORESIS - Millan Scarabeli Alves Coelho da Silva; Francisco José Penna; Ricardo Jenner Duarte; Pedro Augusto Rocha Pereira; Andreia Elisa Cursino; Luciano Amedée Péret-Filho; Edilberto Nogueira Mendes; Paula Prazeres Magalhães (Revista do Instituto de Medicina Tropical de São Paulo, 2013)
Rotavirus has been considered the main agent of infectious diarrhea especially among younger children. We addressed the prevalence of rotavirus-associated diarrhea and the diversity of circulating electropherotypes by immunochromatography and RNA electrophoresis. Stool samples were taken from 391 children (267 with diarrhea) from the lower socioeconomic stratum who sought treatment in the Hospital Infantil João Paulo II/Belo Horizonte, during 2005 and 2006. Rotavirus was detected in 79/20.2% of subjects, 64/24.0% with diarrhea and 15/12.1% with no diarrhea. The virus was strongly associated with diarrhea (p = 0.003). A total of 76/19.4% and 69/17.6% rotavirus-positive children were identified by immunochromatography and electrophoresis, respectively. Rotavirus-associated diarrhea was more frequently detected in dry months (p < 0.001) and almost exclusively in children aged up to three years. Long profile strains prevailed (54/78.3%) but a shift toward short electropherotype was identified. Despite the decrease seen in 2006, rotavirus infection is still very common in our area. Although viral RNA electrophoresis is useful as a typing method, it should not be used exclusively in the diagnosis of rotavirus infection. We confirmed a shift from long to short profile strains, as already described for other South American countries.